Adjuvant Dose-Dense Chemotherapy in Breast Cancer: Standard of Care in High-Risk Patients - Möbus, Volker (Breast Care (Basel), 2016)
Meta-analyses persistently confirm the superiority of dose-dense chemotherapy in comparison with standard chemotherapy. In contrast, individual studies have shown conflicting results. These may be explained by different risk profiles of the treated patient populations. Some trials show a significant advantage in disease-free survival (DFS) and overall survival (OS) in the estrogen receptor (ER)-negative population only, whereas trials with high-risk populations like GIM-2 (Gruppo Italiano Mammella) and AGO-iddETC (Arbeitsgemeinschaft Gynäkologische Onkologie, intense dose-dense epirubicin, paclitaxel, and cyclophosphamide) show a significant superiority in DFS and OS for both, ER-negative and ER-positive patients even after 7 and 10 years, respectively, of follow-up. In contrast, the 10-year follow-up data of the E1199/Intergroup trial no longer showed any superiority of weekly paclitaxel for ER-positive/HER2-negative patients; superiority was observed in the triple-negative subgroup only. Although a direct head-to-head comparison is missing, iddETC or 4 cycles each of dose-dense epirubicin/cyclophosphamide followed by paclitaxel are the preferred adjuvant regimens for patients at risk. Patients with ≥ 4 positive lymph nodes should preferentially be treated with iddETC.